Development of functional molecular markers for viviparous germination resistance in rice - Lee, So-Myeong; Kwon, Youngho; Kim, Sung-Ryul; Kang, Ju-Won; Park, Hyeonjin; Cha, Jin-Kyung; Park, Dong-Soo; Cho, Jun-Hyun; Kim, Woojae; Eom, Gyu-Hyeon; Lee, Jong-Hee (MDPI, 2024)
Rice (Oryza sativa) plays a pivotal role in global food security. Understanding the genetics of rice cultivation is crucial, particularly for traits such as viviparous germination, which significantly influences germination and yield. Our research aimed to elucidate the genetic and molecular mechanisms by which the Sdr4 gene influences viviparous germination and to develop novel molecular markers for this gene to enhance breeding strategies against viviparous germination. In all, 683 rice cultivars and 100 F2 plants were used for viviparous germination and genetic analysis using KASP (Kompetitive Allele-Specific PCR) and agarose gel-based markers related to viviparous germination tolerance. We developed and used a polymorphic agarose gel-based marker and a KASP marker targeting the Sdr4 gene. A genetic analysis of field-grown rice cultivars and the F2 population revealed that the two markers on Sdr4 were functional for the genomic selection of SNPs and InDels related to dormancy. The Pearson correlation coefficient (r = 0.74, p-value = 3.31 × 10−8) between the Sdr4-IND KASP marker genotype and viviparous germination rate demonstrated a significant positive correlation, supporting the marker’s utility for selecting rice varieties with diminished viviparous germination. This insight serves as a critical theoretical foundation for breeding strategies for developing early-maturing rice varieties with enhanced resistance to viviparous germination, addressing pivotal challenges in rice cultivation, and ensuring food security.